Association between hemoglobin-to-red cell distribution width ratio and occurrence of sepsis during ICU stay in inflammatory bowel disease patients who died: a retrospective study using the EICU-CRD database - Yulin Li; Qian Hua; Zhengyang Li; Miao Jiang (PLoS ONE, 2026)
Background The hemoglobin-to-red cell distribution width ratio (HRR) is a biomarker associated with systemic inflammation and outcomes in critical illness. Within clinical databases, there exists an extreme-prognosis subgroup of inflammatory bowel disease (IBD) patients, those who all died within 30 days of ICU admission. Due to limitations in the database, this study can only analyze this specific subgroup. Objective This study aims to explore and describe the association between admission HRR and the occurrence of sepsis during ICU stay in this specific subgroup of IBD patients. Methods A retrospective cohort study was conducted using the eICU Collaborative Research Database (2014–2015), including 229 eligible patients. Multivariable logistic regression was used to assess the independent association, adjusting for confounders. The dose-response relationship was examined using restricted cubic spline (RCS) models. Subgroup and interaction analyses were performed across age, sex, and race. Results The sepsis group had a significantly lower admission HRR than the non-sepsis group (6.04 ± 1.66 vs. 6.77 ± 2.0, P = 0.008). After full adjustment, each 1-unit increase in HRR was associated with 20.3% lower odds of sepsis (P = 0.007). Compared to the lowest quartile (HRR < 5.1), patients in the highest quartile (HRR ≥ 7.85) had 66.8% lower adjusted odds of sepsis (P = 0.015). RCS analysis indicated a linear, inverse relationship between HRR and sepsis (P for non-linearity = 0.42). Subgroup analysis revealed the negative association was more pronounced in patients aged <65, males, and White patients. However, formal interaction tests were not statistically significant (all P for interaction >0.05), indicating the association did not differ meaningfully across these subgroups. Conclusions In this specific cohort, a lower admission HRR was associated with the occurrence of sepsis. Due to inherent selection bias, this finding describes an association within this specific subgroup and cannot be generalized. This exploratory study generates the hypothesis that HRR may reflect a unique pathophysiological state in end-stage IBD, a hypothesis that requires validation in prospective, unbiased cohorts.